1987
DOI: 10.1002/app.1987.070330217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal history on mechanical properties of polyetheretherketone below the glass transition temperature

Abstract: SynopsisTensile properties of polyetheretherketone (PEEK) have been studied at 125, 25, and -100°C for thin films prepared with different therxnal histories. Initial morphology was controlled by rate of cooling from the melt. Amorphous films resulted from quenching the melt, while semicrystalline films were obtained by cooling the melt at Merent rates, or by crystallization of the rubbery amorphous state. The films were characterized using density, X-ray scattering, differential scanning calorimetry, and infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 2 publications
6
90
0
Order By: Relevance
“…• C), attributed to the β relaxation [45], associated with local motions of the ketone groups, and an intense sharp peak (at 148.3…”
Section: Dynamic Mechanical Propertiesmentioning
confidence: 99%
“…• C), attributed to the β relaxation [45], associated with local motions of the ketone groups, and an intense sharp peak (at 148.3…”
Section: Dynamic Mechanical Propertiesmentioning
confidence: 99%
“…The early reports of this technique by Cebe [51] and Chalmers [49] has been refined by Jones and Legras [52] who have shown that PEEK crystallinity can be evaluated by comparing the absorbance area ratio of the 947 cm −1 band to the 1,011 or 952 cm −1 reference bands. Although these three methods have been widely used to examine the morphology of PEEK and its composites, the reader should be aware that such data may be subject to systematic biases, and hence must be interpreted with caution.…”
Section: Crystalline Structure Morphology and Thermal Transitionsmentioning
confidence: 99%
“…PEEK is a semi-crystalline thermoplastic polymer with excellent thermal and chemical stability [10], currently used in a wide range of applications [11], especially for the automobile and aerospace industries. Since its commercialization in 1981, many studies have been reported on the structural [12], thermal [13] and mechanical [14] characterization of this high-performance thermoplastic material. In the literature there are many reports related to the integration of SWCNTs into polymer matrices [15,16], but only a few papers deal with such composites with a PEEK matrix; the most relevant being those published by Shaffer and co-workers [17,18], working with carbon nanofibres/PEEK composites and by Baaba et al [19], dealing with multi-walled nanotubes functionalized with sulfonated PEEK.…”
mentioning
confidence: 99%